2021
DOI: 10.3390/v13071328
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Abundance of Culicoides stellifer, a Candidate Orbivirus Vector, Indicates Nonrandom Hemorrhagic Disease Risk for White-Tailed Deer (Odocoileus virginianus)

Abstract: (1) Background: Hemorrhagic diseases in white-tailed deer (Odocoileus virginianus) are caused by orbiviruses and have significant economic impact on the deer ranching industry in the United States. Culicoides stellifer is a suspected vector of epizootic hemorrhagic disease virus (EHDV), with recent field evidence from Florida, but its natural history is poorly understood. Studying the distribution and abundance of C. stellifer across the landscape can inform our knowledge of how virus transmission can occur lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The high overall EHDV seropositivity (57.87%) suggested that EHDV infection in cattle is widely spread in different regions of Guangdong, and the seropositive rate is significantly higher than other regions of China [ 16 ]. Previous studies indicated that the circulation dynamics of EHDV depend on the vector population abundance and vitality, which are largely influenced by climatic factors such as temperature, precipitation, wind, and humidity [ 34 , 35 ]. Guangdong province has a typical subtropical climate that is characterized by high temperature over the whole year, abundant rainfall, and high humidity, thus making it a preferred habitat of Culicoides species [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The high overall EHDV seropositivity (57.87%) suggested that EHDV infection in cattle is widely spread in different regions of Guangdong, and the seropositive rate is significantly higher than other regions of China [ 16 ]. Previous studies indicated that the circulation dynamics of EHDV depend on the vector population abundance and vitality, which are largely influenced by climatic factors such as temperature, precipitation, wind, and humidity [ 34 , 35 ]. Guangdong province has a typical subtropical climate that is characterized by high temperature over the whole year, abundant rainfall, and high humidity, thus making it a preferred habitat of Culicoides species [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Water features on the ranch included one large pond (2.3 ha), two small ponds (0.35 ha and 0.1 ha), and a permanent stream fed by spring seepages. There were also 10 double-fenced WTD breeding pens within a larger exclusion zone totaling ~9.3 ha [34]; hunting preserve animals were excluded from the entire breeding pen area. The primary habitat type of the ranch was hardwood hammock with upland short-leaf pine species, such as loblolly pine (Pinus taeda), growing throughout the ranch [34].…”
Section: Study Areamentioning
confidence: 99%
“…Combining these unknowns with the expanding distributions of these viruses puts both naïve domestic livestock and wildlife species in previously unaffected areas at risk of more severe and more frequent outbreaks. Current research efforts by ours and various other teams around the world [31][32][33] are working to define the ecology of Culicoides vectors, namely their seasonal abundance, host, and habitat preferences, as identifying these details can help understand the expansion of HD viruses [34]. With this knowledge, we may be able to proactively manipulate herd habitat use to avoid specific areas at times of high vector abundance [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The seasonality of adult midges is also dependent on species and geography. The common ecological drivers of adult Culicoides abundance include warm springs and autumns, higher precipitation, humidity, proximity to aquatic sources, and proximity to hosts such as cattle and sheep [19][20][21][22]. Evaluating midge abundance is accomplished primarily by trapping adult insects using carbon dioxide-baited traps, light traps, or combinations of these [23].…”
Section: Culicoides Biting Midgesmentioning
confidence: 99%